Fluoroscopy Is Essential in Retrograde Intrarenal Surgery - Mehmet Yoldas; Tuba Kuvvet Yoldas (International Journal of Clinical Practice, 2023)
Objective. This study aimed to investigate the necessity of using fluoroscopy in retrograde intrarenal surgery (RIRS). Material and Methods. A total of 612 patients who underwent RIRS for kidney stones were evaluated and divided into two groups. Group 1 routinely underwent the operation with fluoroscopy due to opaque stones (n: 504). In group 2, the procedure was performed without fluoroscopy because of nonopaque stones (n: 108). Both groups were assessed for stone size, location, and number. Success and complication rates were compared between the two groups. Conclusion. This study was designed with the thought of not using fluoroscopy in RIRS patients with nonopaque stones and having the same stone-free rates in opaque stones. In the statistical analysis, there was no difference between the groups with and without scope for stone side, size, localization, and number; likewise, the complication rates developed in the comparison of both groups, stone-free rates, and hospital stay were the same. Discussion. Advances in the calibration of instruments, the development of optical systems, and improvements in imaging system resolution have gradually reduced the need for fluoroscopy in RIRS. This study provides further evidence that fluoroscopy is unnecessary in RIRS procedures, thereby eliminating unnecessary radiation exposure.